Sex differences in the association between waist circumference and physical fitness index among Tajik adolescents in the Pamir Mountains of Xinjiang, China: an observational study - Yuanjiao Chen; Ruibao Cai; Di Chai; Huipan Wu (BMC Sports Science, Medicine and Rehabilitation, 2024)
Abstract Background It has been reported in the literature that waist circumference (WC) was related to physical fitness in adolescents. However, the association between WC and PFI(physical fitness index), a comprehensive indicator of physical fitness, has been less studied. In addition, it is not clear whether the association between WC and PFI changes depending on altitude, ethnicity, and sex. This study further revealed the correlation between WC and PFI among adolescents in high-altitude areas and provided references for the physical and healthy development of adolescents in high-altitude areas. Methods In this study, a total of 1705 Tajik adolescents aged 13–15 years were selected using stratified whole-population sampling. WC and physical fitness items (grip strength, standing long jump, 50 m dash, and endurance run) were assessed and a standardized method was used to calculate PFI. The association between WC and PFI was analyzed by curvilinear regression analysis. Results The mean and standard deviation of WC and PFI for Tajik adolescents aged 13–15 years old on the Pamir Plateau in Xinjiang, China, were 68.26 ± 7.75 cm and − 2.00 ± 3.47 respectively. Comparison of PFI between groups of Tajik adolescents with different WC showed that inter-group comparisons had significant effects with effect size above 0.2. The Tajik adolescents’ PFI reached its highest when WC was 61 cm for boys(-1.3207), and 60 cm for girls (-1.0556). Conclusions The association between WC and PFI in Tajik adolescents showed an inverted “U” curve, with no sex difference. It is recommended that the WC of Tajik adolescents should be controlled between 60 and 61 cm to maintain better PFI levels. The study provides support and reference for educational policy-making and public health prevention in the Pamir Plateau in Xinjiang, China.